(untitled) (Journal of the College of Basic Education, 2025)
This research deals with the narrative and analysis of the Renaissance Dam project on the Blue Nile and the position of the Gulf Cooperation Council countries towards it, the construction of which raises a lot of controversy in political circles as it greatly affects the water security of the downstream countries, especially Egypt, which has been greatly reflected in its foreign policy. The research attempts to shed light on the Renaissance Dam project and the development projects associated with it. And to know the size and form of internal and external support and funding in the construction of the Renaissance Dam and its impact on Egyptian water and national security. It also tracks the position of the Gulf Cooperation Council countries on the stages of building the dam and its impact on the form and nature of the Gulf-Egyptian-Sudanese relations on the one hand and the Gulf-Ethiopian relations on the other hand.